Study of The Technical Approach on Recent Fuel Efficiency to Reduce Ship Emissions - Mohammad Danil Arifin; Frengki Mohamad Felayati; Fanny Octaviani (Institut Teknologi Sepuluh Nopember, 2022)
Engine emissions of ships have been highly concerned in the last decades. Most of the current ship operations worldwide are powered by the combustion engine. Advance ship powering is still on research and hard to implement directly. High cost in the application is the main issue. Meanwhile, the fuel engineering approach is proposed in the recent research to advance engine combustion, thus increasing the combustion efficiency and lowering the emissions target. This study aims to evaluate the development trend on the fuel efficiency technique to lower ship emissions. Emissions management, fuel conversion, and power conversion are the most research focus to improve fuel efficiency. However, implementing some of that research is still hard on ship operation. Technical and economic issues are the main reason. Moreover, fuel efficiency on ships is still highly based on management. Low cost, new combined fuel without separation, and less fuel treatment technology are proposed to avoid confusion on fuel consumption in the near future.